"Uruk Expansion": Early Cities, Trade Networks and Colonization in Mesopotamia During 4th Millennium BCE. - İzzet ÇIVGIN (International Journal of Eurasia Social Sciences, 2015)
The present study discusses the effects of cross-cultural contact between lower and upper Mesopotamia, during so-called “Uruk expansion” (widespread distribution of southern Uruk-style material culture at sites at the North) in the 4th millennium BCE. The aim of this paper is to find answers to these 5 questions: 1- What were the underlying causes for “Uruk expansion”: Was it an attempt to control important trade routes or a pursuit of fertile lands suitable for farming? 2- Was there an asymmetrical exchange between southern city-states and northern non urban societies? 3- Was there a kind of world-system in which the core dominates the periphery and controls long-distance exchange? 4- What were the effects of cross-cultural exchange in early Mesopotamian civilization? 5- What can be said about the interregional interactions during the Uruk period that can take a variety of different but often overlapping forms such as exchange, colonization and emulation?